2019
DOI: 10.1002/jgh3.12141
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: Safety and efficacy of local injections of mesenchymal stem cells in perianal fistulas

Abstract: Perianal fistulas in Crohn's disease (CD) represent a highly debilitating and difficult‐to‐treat condition. Given emerging supportive evidence, we conducted a systematic review and meta‐analysis of all trials/observational studies to establish the safety and efficacy of local injections of mesenchymal stem cells (MSCs). The PRISMA‐P statement was applied for planning and reporting, and MEDLINE, EMBASE, Web of Science, Cochrane, CINAHL, ClinicalTrials.gov database, and ECCO 2017 proceedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 65 publications
1
18
0
1
Order By: Relevance
“…Recently, several studies about fistula curettage and mesenchymal stem cell therapy have been published and analyzed in a recent recent systematic review and metaanalyis (23 studies with 696 patients) [75], showing significant results concerning fistula closure (overall 80% success rate). However, the 4 randomized controlled trials (483 patients) revealed a closure rate of 64% (vs. 37% in the control arm).…”
Section: Therapy Algorithm For Fistulizing Diseasementioning
confidence: 99%
“…Recently, several studies about fistula curettage and mesenchymal stem cell therapy have been published and analyzed in a recent recent systematic review and metaanalyis (23 studies with 696 patients) [75], showing significant results concerning fistula closure (overall 80% success rate). However, the 4 randomized controlled trials (483 patients) revealed a closure rate of 64% (vs. 37% in the control arm).…”
Section: Therapy Algorithm For Fistulizing Diseasementioning
confidence: 99%
“…Moreover, fistula healing was maintained in most cases (56.3%) at 1 year (Panés et al, 2018), although further studies showed that the proportion of patients relapsing upon a longer follow‐up increased over time (Ciccocioppo et al, 2015). Importantly, no safety concerns were reported, thus confirming the tolerability of the treatment, while, again, a sustained increase of regulatory T‐cells was invariably observed in those cases where it was investigated (Ciccocioppo, Klersy, et al, 2019).…”
Section: Mesenchymal Stem/stromal Cells (Mscs) As Adoptive Cell Immunmentioning
confidence: 58%
“…Clearer and more unambiguous results were obtained when using MSC local injections for fistulizing refractory Crohn's disease. This new treatment option gave excellent results in terms of both safety and efficacy (Ciccocioppo et al, 2019). Notably, the results of the first phase III multicentre trial, where 212 patients were enrolled and randomly assigned to receive a single local injection of an industrial preparation of allogeneic adipose tissue derived‐MSCs (Darvadstrocel, formerly Cx601®) or placebo, showed that MSCs performed better than placebo to achieve combined remission (51.5% vs. 35.6% at week 24) within a shorter period of time (Panés et al, 2016).…”
Section: Mesenchymal Stem/stromal Cells (Mscs) As Adoptive Cell Immunmentioning
confidence: 99%
“…18,19 In this regard, it should be emphasized that MSC administration may be performed by using different routes: intravenously with access from a peripheral or central vein, intra-arterial depending on the target organ, but also directly in the damaged tissue as in fistulizing Crohn's disease where local injections have proved successful in inducing closure of fistula tracks refractory to standard treatment. 67 Additionally, delivery routes such as intrathecal, intra-articular, and intradermal have been shown feasible in patients suffering from amyotrophic lateral sclerosis, osteoarthritis, and scleroderma, respectively. [68][69][70] It is conceivable therefore, that also in the case of COVID-19 patients, intratracheal administration might work better.…”
Section: Mscs Can Attenuate Covid-19 Related Cytokine Storm and Coagulopathymentioning
confidence: 99%